PERBEDAAN PRESTASI BELAJAR ANAK USIA SEKOLAH PADA PEMBELAJARAN MEMBACA, MENULIS, BERHITUNG (CALISTUNG) DINI DI SD KATOLIK HATI KUDUS RAJAWALI MAKASSAR - Fransiska Anita (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2019)
Learn to reading, writing, arithmetic when early age has become a common thing among people. This study aimed to determine the differences in learning accomplishment for children who received the reading, writing, arithmetic earlier and did not receive reading, writing, arithmetic earlier at Hati Kudus Rajawali Elementary School Chatolic of Makassar. The research design was non-experimental study comparative approach. The total sample of 40 respondents with consecutive sampling technique. The independent variable was early learning, reading, writing, arithmetic and the dependent variable were the learning accomplishment. The analysis showed differentiation in learning achievement of the school-age children in the early learning, reading, writing, arithmetic the results of the Mann-Whitney test p = 0.027 (p <?). These results revealed the differentiation between the mean learning accomplishment in the group that received early reading, writing, arithmetic and the group that did not receive early learning, reading, writing, arithmetic. Conclusion: Students who receive an early age reading, writing, arithmetic time will show lower learning accomplishment than students who did not receive an early learning reading, writing, arithmetic.